The role of information in the application for merit-based scholarships: Evidence from a randomized field experiment - Stefanie P. Herber (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
If information asymmetries prevent talented students of non-academic backgrounds from applying for merit-based aid, the full potential of qualified youth will not be unfolded and social selectivity is likely to corroborate. This paper analyzes whether information asymmetries exist and decrease students' likelihood to apply for merit-based scholarships. In a randomized field experiment, I expose more than 5,000 German students either to general information on federally funded scholarships or additionally to tailored information on details of the application process, conveyed by a similar role model. Both treatments reduced information asymmetries significantly. The role model treatment did significantly increase non-academic and male students' application probabilities for federally funded merit-based scholarships. Providing only general information on the scholarship system triggered participants' own information search for alternative funding sources and increased application rates for other, not federally funded scholarships.
Keywords: I22; I24; D83; 330; information asymmetries; student financial aid; merit scholarships; role model; field experiment